2011
DOI: 10.1103/physreve.83.056404
|View full text |Cite
|
Sign up to set email alerts
|

Classical relativistic model for spin dependence in a magnetized electron gas

Abstract: The response of a cold electron gas is generalized to include the spin of the electron described by the relativistically correct quasiclassical Bargmann-Michel-Telegdi (BMT) equation. The magnetization of the electron gas is assumed to be along the background magnetic field B and the spin-dependent contribution to the response tensor is proportional to the magnitude of the magnetization. The dispersion equation is shown to be quadratic in the refractive index squared, and dispersion curves for the two wave mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Thus, a semi-classical kinetic theory, as the one constructed here, is useful to obtain the first-order quantum corrections to descriptions of strongly magnetized plasmas. Examples are pulsar atmospheres [48][49][50] or high-energy laser-plasmas [51], where quantum effects have been found to be very relevant at high energies [52][53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, a semi-classical kinetic theory, as the one constructed here, is useful to obtain the first-order quantum corrections to descriptions of strongly magnetized plasmas. Examples are pulsar atmospheres [48][49][50] or high-energy laser-plasmas [51], where quantum effects have been found to be very relevant at high energies [52][53][54][55][56].…”
Section: Discussionmentioning
confidence: 99%
“…10 Using a classical relativistic model, the properties of waves in a cold magnetized electron gas including the effect of spin dependence were proposed by Ref. 24. Oraevsky and Semikoz 25 have examined the spin waves in dense magnetized plasma and found the growth rate of the electromagnetic spin waves in the presence of intense quasimonoenergetic fluxes of neutrinos.…”
Section: Introductionmentioning
confidence: 99%
“…It was also shown that the electron spin-1/2 modifies the shape of the magnetosonic solitary waves. A classical relativistic model for spin dependence in a magnetized electron gas has been proposed by Melrose and Mushtaq [12], where a generalize theory of wave dispersion has been constructed for cold electron gas by using a relativistically correct quasiclassical Bargmann-Michel-Telegdi (BMT) equation. In the MHD limit, spin Alfvén solitons were investigated in magnetized electron-positron plasmas [13] by deriving a modified KdV equation.…”
Section: Introductionmentioning
confidence: 99%